Tests to determine the form of lathe tool to remove maximum metal with minimum power from gray iron - Rhodes, Arthur J. (My University, 1905)
Introduction: The object of the tests performed was to determine which form of lathe tool will remove, from gray iron, maximum metal with minimum power. That is to say; to ascertain approximately what should be the proper angle of rake and clearance for lathe tools, and whether the tool should be round or diamond nose, to remove the most metal with the least power. To determine the power it would take to drive the lathe, a Briggs transmission dynamometer of the belt pattern was used. This dynamometer is from the K. S. A. C. laboratory, an elevation of this type of machine is given in figure (1). The power is transmitted through the dynamometer, to the machine performing the work, without being absorbed by the dynamometer. When the dynamometer comes to rest, or is running with no outside resistance, the system will come into equilibrium with equal but opposite angles for both the lower and upper belt, provided the weight of the carrier pulleys (a & b) figure (1), the frame supporting same, and the weight of the belt are balanced.
Citation: Rhodes, Arthur J. Tests to determine the form of lathe tool to remove maximum metal with minimum power from gray iron. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Dynamometer; Prony Brake; Brake Pulley; Horse Power; Theses